2008
DOI: 10.1016/j.cmet.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Stimulates Glucose Utilization in Normal and Obese Insulin-Resistant Mice

Abstract: Adipose tissue (AT) secretes several adipokines that influence insulin sensitivity and potentially link obesity to insulin resistance. Apelin, a peptide present in different tissues, is also secreted by adipocytes. Apelin is upregulated in obese and hyperinsulinemic humans and mice. Although a tight relation exists between the regulation of apelin and insulin, it remains largely unknown whether apelin affects whole-body glucose utilization. Herein, we show that in chow-fed mice, acute intravenous injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
389
3
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(444 citation statements)
references
References 29 publications
22
389
3
16
Order By: Relevance
“…It also explains the previous observations in mice that apelin treatment leads to a significant decrease in plasma lipid hydroperoxide (an index of systemic oxidative stress) (23), and improves glucose uptake in adipose tissue (18). Dray et al has demonstrated that intravenous injection of apelin has a powerful effect to enhance glucose utilization in skeletal muscle and adipose tissue in high-fat fed obese and insulin-resistant mice (20). As reported in this study, endothelial NO synthase (eNOS) activation is essential to apelin's effect on skeletal muscle (20).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…It also explains the previous observations in mice that apelin treatment leads to a significant decrease in plasma lipid hydroperoxide (an index of systemic oxidative stress) (23), and improves glucose uptake in adipose tissue (18). Dray et al has demonstrated that intravenous injection of apelin has a powerful effect to enhance glucose utilization in skeletal muscle and adipose tissue in high-fat fed obese and insulin-resistant mice (20). As reported in this study, endothelial NO synthase (eNOS) activation is essential to apelin's effect on skeletal muscle (20).…”
Section: Discussionmentioning
confidence: 48%
“…Dray et al has demonstrated that intravenous injection of apelin has a powerful effect to enhance glucose utilization in skeletal muscle and adipose tissue in high-fat fed obese and insulin-resistant mice (20). As reported in this study, endothelial NO synthase (eNOS) activation is essential to apelin's effect on skeletal muscle (20). eNOS activity is also important for glucose uptake in adipocytes (71,72).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Glucose transport in ex vivo muscle Glucose transport was measured as previously described [29]. Soleus muscles were isolated and preincubated for 10 min in KH buffer, pH 7.4, containing BSA (2 mg/ml), 2 mmol/l sodium pyruvate and 20 mmol/l HEPES.…”
Section: Methodsmentioning
confidence: 99%
“…Circulating apelin increases in obesity 56 and has been show to lower glucose in normal and obese mice. 57 Homozygous apelin knockout mice have severe heart failure in response to pressure overload and diminished heart contractility in aged mice, 58 indicating a role for the adipokine in maintaining cardiac function. Visfatin is an adipokine that is predominantly expressed in visceral adipose tissue and has been attributed to having insulin-like properties, 59 although this has since been disputed, 60,61 and recently visfatin has been shown to have pro-inflammatory effects.…”
Section: Adipose Tissue a Paracrine And Endocrine Organmentioning
confidence: 99%